2013
DOI: 10.1007/s00417-013-2514-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and morbidity of contact lens–associated microbial keratitis: a retrospective study

Abstract: Microbial keratitis is a serious complication of contact lens wear, with approximately one out of five hospitalized cases requiring corneal transplantation. Ofloxacin, or a combination of gentamicin and cephazolin, still appear to be excellent first-choice therapies in the Netherlands, as little resistance has developed to these antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 24 publications
8
54
0
Order By: Relevance
“…Our results are close to those reported in the majority of series [1] [3]. The corneal abscess was unifocal in 24 cases (86.2%) and centrally located in 20 cases (69%) with an average diameter of 3.9 mm (range: 1to10 mm).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are close to those reported in the majority of series [1] [3]. The corneal abscess was unifocal in 24 cases (86.2%) and centrally located in 20 cases (69%) with an average diameter of 3.9 mm (range: 1to10 mm).…”
Section: Discussionsupporting
confidence: 89%
“…This period was less than or equal to 7 days in 69% of cases. In the literature, the average consultation period was 4.6 days in the Netherlands as discussed by Hoddenbach [1], 2 days in France as cited by Bourcier [13] and 5 days in a Moroccan study realized by Benhmidoune and et al [3]. The corneal abscess in our series was unilateral in all cases (100%).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…This infection can be managed and treated with a course of antibiotics such as second-generation fluoroquinolones, Moxifloxacin and Gatifloxacin. [108][109][110] The retrospective study conducted by Johan et al, 111 at Rotterdam Eye Hospital evaluated the epidemiological characteristics, clinical presentation, isolated organism, and treatment for all hospitalised patients with CLMK. The study also revealed that more than 65% of the isolated microorganisms were Pseudomonas aeruginosa with 2.7% and 1.3% resistance to gentamicin and ofloxacin respectively.…”
Section: Contact Lens-associated Microbial Keratitis (Clmk)mentioning
confidence: 99%
“…The study also revealed that more than 65% of the isolated microorganisms were Pseudomonas aeruginosa with 2.7% and 1.3% resistance to gentamicin and ofloxacin respectively. 111 Almost 65% of the admitted cases showed best corrected visual acuity (BCVA) lower than 0.05 Snellen. Other pathogens such as acanthamoeba and fungi were also reported to be associated with CLMK.…”
Section: Contact Lens-associated Microbial Keratitis (Clmk)mentioning
confidence: 99%